La temporalité et les procédés narratifs dans les toy books de Walter Crane - François Fièvre (Strenae)
By closely examining the narrative workings of the "Sixpenny Series" toy books illustrated by Walter Crane between 1865 and 1876, we will distinguish between different types of temporalities: iconic, intericonic, and intericonotextual. Pulling from the conventions of historic paintings and experimenting with the emerging comic strip, Walter Crane is situated in an in-between period still in its infancy, which vacillates between allegorical “monstration” and narrative sequencing, and which multiples the processes of image temporalization and the relationship between text and image. All this contributes to the complexity of reading his work, which teaches us how the reading conventions of today's children's books were born in the past.